Distribution and partial characterisation of IgG Fc binding protein in various mucin producing cells and body fluids. Issue 2 (1st August 2002) - Kobayashi, K; Ogata, H; Morikawa, M; Iijima, S; Harada, N; Yoshida, T; Brown, W R; Inoue, N; Hamada, Y; Ishii, H; Watanabe, M; Hibi, T
Abstract : Background and aims: Mucus released from goblet cells is important in intestinal mucosal defence, and mucin glycoproteins are thought to be major components of mucus. Recently, we identified and cloned another component of human colonic mucus, IgG Fc binding protein (FcγBP). FcγBP is immunologically distinct from known Fcγ receptors and its structure contains repeated cysteine rich unit sequences resembling those present in mucins. In this work, we assessed the tissue distribution of FcγBP, its binding activity in various body fluids, and its ability to inhibit complement mediated haemolysis. Methods: Immunohistochemical localisation of FcγBP, using monoclonal antibodies against FcγBP (K9 or K17) and labelled IgG, was conducted in various mucin producing tissues: colon, small intestine, stomach, gall bladder, cystic duct, choledochus, bronchus, submandibular gland, conjunctiva, and cervix uteri. The binding activity of FcγBP in mucus extracted from colon, gastric juice, bile, nasal discharges, saliva, sputum, and tears was also examined by immunodotblot and immunoprecipitation using these monoclonal antibodies. Inhibition of complement mediated haemolysis by FcγBP was investigated using sheep red blood cells (SRBC) and anti-SRBC IgG. Results: The immunohistochemical study revealed that mucin secreting cells in the colon, small intestine, gall bladder, cystic duct, choledochus, bronchus, submandibular gland, and cervix uteri contained FcγBP, and immunodotblot and immunoprecipitation analysis using IgG and monoclonal antibodies demonstrated that the fluids secreted by these cells were capable of binding IgG. Mucin producing cells of the conjunctiva did not express FcγBP molecules or bind to IgG. The surface mucus cells in the stomach were variably positive for FcγBP. Perhaps because of proteolytic degradation, FcγBP in gut lavage fluid did not have IgG binding activity, although this activity was present in the mucus covering the colon. FcγBP suppressed complement mediated haemolysis of SRBC. Conclusions: FcγBP is widely expressed on mucosal surfaces and in external secretions. It is functionally intact in several fluids. These findings lend support to the concept that FcγBP is an important component of mucosal immunological defences.